Developing a Digital Book of Proficiency in Writing Scientific Articles with Artificial Intelligence to Improve Elementary Education Students' Scientific Writing Skills - Batubara, Hamdan Husein (Universitas Islam Lamongan, 2025)
The connectivistic learning theory emphasizes the pivotal role of technology in enhancing students' access to resources and skills, particularly in scientific writing. This study employs the ADDIE model to develop a digital book designed to improve the scientific writing competencies of elementary education students. A needs analysis indicated that students have a limited understanding of research methodologies and academic writing, with an average proficiency rate of only 45%. They expressed moderate difficulty in writing scientific articles and requested the development of a user-friendly and visually engaging digital book. In response to these findings, we produced an innovative digital book in HTML5 and PDF formats, featuring clearly defined learning objectives, AI-integrated materials, concise summaries, project assignments, and interactive quizzes. The content encompasses guidance on writing articles, examples of scientific article structures, and techniques for utilizing AI in writing. Validation by five experts yielded a score of 4.35 out of 5, affirming the material's strong content and presentation quality. A pilot study conducted with 26 students demonstrated a high usability score of 4.60, indicating that the digital book effectively enhances students' comprehension and motivation in scientific writing. The results suggest that integrating Project-Based Learning (PjBL) and AI tools can substantially improve students' writing skills and facilitate their navigation through academic challenges